Nota sobre culicídeos (Diptera: Culicidae) da bacia do rio Purus, Acre, Amazônia (Brasil) Note on the culicidae (Diptera: Culicidae) of the River Purus Basin, Acre, Amazonian, Brazil - Delsio Natal; José Maria Soares Barata; Carmen Beatriz Taipe Lagos; Roraima Moreira Rocha (Universidade de São Paulo, 1992)
Foram feitas coletas de mosquito (Diptera: Culicidae) na área do projeto de Colonização Pedro Peixoto, no Estado do Acre, Brasil. Obteve-se um total de 4.588 exemplares pertencentes a 53 espécies ou grupos. Salienta-se a ocorrência de Anopheles (Nyssorhynchus) oswaldoi. Mosquito (Diptera: Culicidae) collections were made on the Pedro Peixoto Colonization Project in the State of Acre, Brazil. Four thousand, five hundred and eighty-eight (4,588) specimens were collected and fifty-three (53) species or group recognised. The occurrence of Anopheles (Nyssorhynchus) oswaldoi is given special emphasis.